Creating a new consensus on population : the international conference on population and development - Singh, Jyoti Shankar (London, 2006)
In 1994, the world's governments agreed far-reaching and enlightened population policies at the International Conference on Population and Development (ICPD) in Cairo. The conference itself, and the many preparatory activities that took place from 1991 to 1994, were characterized by intense debate on the politics of population and development, reproductive health and rights, religion, contraception and the empowerment of women. This volume explores the whole ICPD process: in particular, how the various stakeholders (governments, NGOs, academic, religious leaders, politicians and the media) addressed the relevant policy issues, and how a new global consensus was forged, resulting in the ICPD Programme of Action.
Keywords: Population